2012
DOI: 10.1007/s00262-012-1384-4
|View full text |Cite
|
Sign up to set email alerts
|

Bi-specific TCR-anti CD3 redirected T-cell targeting of NY-ESO-1- and LAGE-1-positive tumors

Abstract: NY-ESO-1 and LAGE-1 are cancer testis antigens with an ideal profile for tumor immunotherapy, combining up-regulation in many cancer types with highly restricted expression in normal tissues and sharing a common HLA-A*0201 epitope, 157–165. Here, we present data to describe the specificity and anti-tumor activity of a bifunctional ImmTAC, comprising a soluble, high-affinity T-cell receptor (TCR) specific for NY-ESO-1157–165 fused to an anti-CD3 scFv. This reagent, ImmTAC-NYE, is shown to kill HLA-A2, antigen-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 51 publications
2
70
0
1
Order By: Relevance
“…Killing assays were carried out with the IncuCyte FLR-Platform (Essen BioScience), as described previously (53,54). Adherent A375 cells were plated at 2 × 10 4 cells per well and incubated overnight at 37°C/5% CO 2 in RPMI-1640 medium supplemented with 10% heat-inactivated FBS and GlutaMAX (Life Technologies) in a 96-well flat-bottom plate.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Killing assays were carried out with the IncuCyte FLR-Platform (Essen BioScience), as described previously (53,54). Adherent A375 cells were plated at 2 × 10 4 cells per well and incubated overnight at 37°C/5% CO 2 in RPMI-1640 medium supplemented with 10% heat-inactivated FBS and GlutaMAX (Life Technologies) in a 96-well flat-bottom plate.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…For instance, McCormack et al (2012) recently reported promising preclinical data investigating the novel immunotherapeutic agent ImmTAC-NYE (Immune-mobilizing monoclonal T-cell receptors Against Cancer-NY-ESO-1). 42 ImmTAC-NYE is a bi-specific fusion protein comprised of a monoclonal T-cell receptor specific for both NY-ESO-1 and LAGE-1 fused with anti-CD3, which activates a potent antitumor T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Of all cancer-testis antigens, MAGE-1 family has obtained growing interest as potential target for different cancers at variable stages [ 169 -173 ]. MAGE-A3 and NY-ESO-1, two cancer-testis antigens, have been used to develop cancer vaccines against melanoma [ 174 -176 ], lung cancer [ 177 ], ovarian carcinoma [ 178 ], and prostate cancer [ 179 ]. In addition to tumor-specifi c antigens, tumorassociated antigens with narrow distribution in tumor cells are widely used in cancer immunotherapy like tumor lysate antigens in DC-loaded vaccines [ 37 , 180 , 181 ].…”
Section: Materials Of Activating Dcs and T Cellsmentioning
confidence: 99%